What Future for the EU in the Global Trading System? - Pascal Lamy (Intereconomics, 2016)
The recent phase of globalisation could be characterised as “wider”, whereas the next phase to come will be “deeper”. This new phase is likely to prove bumpier than the previous one, as the issues now at stake will have more to do with values or ethics, the interpenetration of which will be both economically necessary and politically difficult. In the medium term, the growth of the European economies will become more dependent on external trade, and thus these policy challenges will need to be addressed.
Keywords: 330; Globalisierung; EU-Staaten